2000
DOI: 10.1002/(sici)1096-8644(200002)111:2<165::aid-ajpa3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and pulmonary responses to high altitude in Quechuas: A multivariate approach

Abstract: This study investigates the relationships among hematological variables, pulmonary function, and age in a sample of high-altitude natives. The following anthropometric and physiological variables were examined in 77 adult Quechua males from the Peruvian Central Andes (Huancavelica, 3,680 m): height, weight, sitting height, chest diameters, chest and abdominal circumferences, forced vital capacity (FVC), forced expiratory volume at 1 sec (FEV1), peak expiratory flow (PEF), hemoglobin concentration (Hb), red blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
6
0
3
Order By: Relevance
“…Among South American highlanders, many studies (Frisancho et al, 1973;Frisancho and Greksa, 1989;Greksa, 1991Greksa, , 1996Mueller et al, 1978;Tarazona-Santos et al, 2000) have reported an increase in lung volume with altitude, especially among the Quechua. In Asia, an increase in FVC in Himalayan Sherpa was observed by Sloan and Masali (1978) and by Majumder et al (1986).…”
Section: Lung Volumementioning
confidence: 99%
“…Among South American highlanders, many studies (Frisancho et al, 1973;Frisancho and Greksa, 1989;Greksa, 1991Greksa, , 1996Mueller et al, 1978;Tarazona-Santos et al, 2000) have reported an increase in lung volume with altitude, especially among the Quechua. In Asia, an increase in FVC in Himalayan Sherpa was observed by Sloan and Masali (1978) and by Majumder et al (1986).…”
Section: Lung Volumementioning
confidence: 99%
“…Several good examples are as follows: 16.1g/dL for adult men living in Nepal, at 3,300masl [39], 18.8g/dL in adult men living in La Paz, Bolivia at 3,700masl [29], 17.5g/dL in adult Peruvians living at 3,680masl [40], 14.5g/dL in Bolivian adolescent girls living at 3,600masl, and 16.6g/dL in Peruvian adolescent girls living at 4,300masl [41]. In this study, the average value corresponds to 14.5g/dL for schoolchildren (boys and girls) who live at 3,240masl.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta fase inicial de exposição à altitude, os indivíduos que apresentam um incremento mais acentuado da ventilação estarão melhor adaptados para tolerar as condições de hipó-xia. A exuberância deste processo adaptativo, isto é, do grau da resposta ventilatória ao estímulo hipóxi-co, apresenta grande variabilidade interindividual parecendo estar associada a diversos factores, tais como o fenótipo e genótipo (31,77). Deste modo, alguns estudos com populações nativas de regiões de elevada altitude (14,15,79), nomeadamente andinas e himalaínas, têm demonstrado que, comparativamente a sujeitos caucasianos residentes ao nível do mar, a sua resposta ventilatória à hipóxia não é tão exuberante.…”
Section: Adaptações Ventilatóriasunclassified